Ethical interlocutions between behavioral-analytic and liberation psychologies: contributions of Skinner and Martín-Baró - Meneses, Glysa de Oliveira; Holanda, Leonardo Carneiro; Ximenes, Verônica de Morais; Santos, Walberto Silva dos (Revista de Psicologia, 2017)
Ethics in relationships, decisions and daily actions is an attribute usually desired by most people. However, it seems sustainable to affirm that all human actions are guided by a specific ethical. Thus, the scientific work is no exception. Since science aims to bring a change in the way of life of individuals, it is up to Ethics to determine how this science is supposed to be applied in order to provide the desired change. In this sense, this article aims to articulate the theory and behavior analysis technology from Skinner and the proposal undertaken by Martín-Baró, especially regarding to ethical aspects. After that, we will analyze how these might be a consistent theoretical framework for the construction of a favorable practice for the promotion of ethical behavior, under this framework, especially in Latin America. The Liberation Psychology propositions constitute a possible secondary value to be used as a guideline for psychologist work to promote the survival of culture, primary ethical value, according to Skinner. In this sense, the integration of different perspectives enables a reflexive movement concerning the psychologists ethical doing.